(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The presents work describes the synthesis and characterization of complexes of Ni (II) with unsubstituted and with substituted (electron releasing as well as electron withdrawing substituent in phenyl nucleus) ligand obtained by coupling of aryldiazonium salt with diethylmalonate. Due to insoluble nature of complexes,[1] H NMR and conductivity data could not be obtained as existence. Since all complexes decomposes before ionization as its melting point are very conclusive evidence could not be obtained by mass spectra. In absence of conductivity data, 1HNMR and mass spectra all the complexes are characterized mainly on the basis of elemental analysis, magnetic moment values, uv-visible spectra and IR Spectra.